CFD modeling of liquid-solid fluidized beds of polydisperse struvite crystals. (February 2018) - Rahaman, Md. Saifur; Choudhury, Mahbuboor R.; Ramamurthy, Amruthur S.; Mavinic, Donald S.; Ellis, Naoko; Taghipour, Fariborz
Highlights: Numerical investigation of the hydrodynamics of a fluidized bed crystallizer. Simulated behaviour obtained from CFD is consistent with the experimental results. Particles found classified according to size, limited intermixing between layers. Volume equivalent diameter represents the particles' characteristic dimension. Provides in-reactor mixing behaviour, eliminating need to pilot test at facility. Abstract: In a liquid-solid fluidized bed crystallization system (having particles of different sizes), two opposite processes (classification and dispersion) influence overall particle size distribution. Interactions between these processes make designing crystallizers challenging, as the solid crystals within the bed exhibit some degree of mixing. Therefore, a better understanding of bed expansion and particle mixing/segregation is required to design fluidized bed crystallizers. In this study, a numerical investigation of the hydrodynamics of liquid-solid fluidized beds of polydisperse struvite crystals was thoroughly performed for the first time. This study also tested and validated three established empirical drag law correlations used to explain momentum exchange between solid and liquid phases. Wen and Yu (1966) and Gidaspow (1994) drag law models showed greater predictive power in terms of pressure drop and voidage in the fluidized beds of multi-particle systems. The simulated bed expansion behavior of different sizes of struvite crystals was found to be consistent with experimental results. At steady state, six different size groups of struvite studied in this investigation were found to be classified according to their sizes with limited intermixing between successive layers.